Evaluation of Imminent Fire Hazards of Inheritance Ancestral Temple and Mansion in Georgetown, Penang - Othuman Mydin, M.A.; Agus Salim, N.A.; Sani, N. Md.; Khaw, Y.Y. (EDP Sciences, 2014)
Fire hazards of the inheritance buildings are often been neglected, causing fire to take place. Most of the heritage buildings are of large scale, flammable priceless contents and large numbers of visitors, however, the existing structures are weak in fire resistance. There are a few factors that contribute to the fire in these unique yet vulnerable structures Therefore, fire risk assessment plays an important role as many historic buildings in Penang are significant in their architectural value and historically importantt and their destructions by fire are great irreplaceable losses. Thus, this study is intended to identify the current fire emergency plan of heritage temples and mansions in Penang which includes 4 buildings such as Khoo Kongsi, Cheah Kongsi, Hock Teik Chen Shin Temple and Teochew Temple. The possible fire risks of these heritage buildings will be identified and evaluated comprehensively. The previous fire cases will be considered as well in order to discover the common factors contributing to the fire cases at heritage buildings. Time and again, people do not record their findings upon completing the fire risk assessment. Hence this particular research will prepare a complete record of the fire risk assessment. Having a fire risk assessment in the heritage building in Penang can be an interesting study to find out the current situation of heritage building fire protection awareness.